Moral skepticisms - Sinnott-Armstrong, Walter, 1955- (Oxford University Press, 2007)
Sinnott-Armstrong here provides an extensive survey of the difficult subject of moral beliefs. He covers theories that grapple with questions of morality such as naturalism, normativism, intuitionism, and coherentism. He then defends his own theory that he calls "moderate moral skepticism," which is that moral beliefs can be justified, but not extremely justified